Oenological Characteristics of Four Non-Saccharomyces Yeast Strains With β-Glycosidase Activity - Qin, Tao; Liao, Jing; Zheng, Yingyuan; Zhang, Wenxia; Zhang, Xiuyan (Frontiers in Microbiology, 2021)
Non-Saccharomyces yeast with β-glucosidase activity might positively contribute to the flavor and quality of wines. To investigate the effects of Issatchenkia terricola SLY-4, Pichia kudriavzevii F2-24, Pichia kudriavzevii F2-16 and Metschnikowia fructicola HX-13 with high β-glucosidase activity on wine, the fermentation process and the flavor and quality of wine fermented by the four non-Saccharomyces yeast strains were analyzed. Compared with S.cerevisiae, the four non-Saccharomyces yeast strains had lower sugar consumption ability, longer fermentation periods, and no significantly negative effect on physicochemical characteristics of wines. Furthermore, they produced lower content of C6 compounds, benzene derivatives and fatty acid ethyl esters, and higher content of terpenes, C13-norisoprenoids, higher alcohols and acetates. Different yeast strains produced different flavor profiles. The four non-Saccharomyces yeast strains produced wines with higher acceptance than S. cerevisiae did, and I. terricola SLY-4 produced wine with the highest acceptance, followed by wines from P. kudriavzevii F2-24, P. kudriavzevii F2-16 and M. fructicola HX-13 from high to low, so they contributed positively to the flavor and quality of wines. The results will provide non-Saccharomyces yeast strains to improve the flavor and quality of wines, and a reference for the selection of other non-Saccharomyces yeasts strains with better oenological characteristics.